Nitrite-reducing ability is related to growth inhibition by nitrite in Rhodobacter sphaeroides f. sp. denitrificans. Issue 1 (2nd January 2018) - Shimizu, Takayuki; Horiguchi, Kouhei; Hatanaka, Yui; Masuda, Shinji; Shimada, Keizo; Matsuura, Katsumi; Haruta, Shin
Abstract: Growth inhibition of Rhodobacter sphaeroides f. sp. denitrificans IL106 by nitrite under anaerobic-light conditions became less pronounced when the gene encoding nitrite reductase was deleted. Growth of another deletion mutant of the genes encoding nitric oxide reductase was severely suppressed by nitrite. Our results suggest that nitrite reductase increases the sensitivity to nitrite through the production of nitric oxide. Abstract: : The lack of nitrite reducing ability (nirK) in a denitrifying purple bacterium increased the tolerance to nitrite under anaerobic lighted conditions.